(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Some areas of improving the management of financial activities of trade enterprises. In the article some directions of perfection of management of financial activity of trading enterprises are analyzed. The process of analyzing its financial condition, research and systematic monitoring of borrowed funds is described. A system of indicators reflecting and characterizing this process is considered. In the work, special attention is paid to the implementation of the requirements for each enterprise to regularly carry out an operative correction of the financial strategy and policies that should be directed to the constant search for new methods and methods of justifying management decisions, as well as the definition and use of new financial instruments for their implementation. At the same time, it is especially important to pay special attention to a comprehensive and reasoned analysis of the financial and economic state of the enterprise, to regularly conduct it in order to improve the existing mechanisms for managing its finances. The necessity of ensuring the implementation and implementation of an integrated approach that provides for system-wide targeted management and balancing of the system at the macro- and micro-level is substantiated. One of the main aspects of the implementation of the above-mentioned problem at the microeconomic level is the provision of effective financial management of trading enterprises. Achievement of financial equilibrium is a priority task of financial management, an adequate solution of which occurs by ensuring the effective functioning of a number of important management subsystems: financial results, solvency, business activity, financial stability and safety of an industrial enterprise, which contributes to its sustainable economic development.